1983
DOI: 10.1111/j.1365-2273.1983.tb01422.x
|View full text |Cite
|
Sign up to set email alerts
|

Aetiological factors in chronic secretory otitis in relation to age

Abstract: The prevelance of chronic secretory otitis media was studied in 5414 children aged 2-12 yr. The maximum incidence of the disease was at the age of 2 yr decreasing progressively to the age of 12, the results fitting a logarithmic curve. Of all the children, 8.7% had chronic otitis media, 0.59% had adhesive otitis and 0.35% chronic suppurative otitis media. The prevalence of secretory otitis was, significantly, related to infections of the upper respiratory tract and to nasal obstruction. The part played by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…Data from these two sources appears to converge. The incidence of OME depends very much on the age of the child [12,13]. Our study shows that in children of school age, irrespective of treatment used, the chance of OME persisting beyond 16 months decreases with age--by 47% for every 2 years.…”
Section: Discussionmentioning
confidence: 68%
“…Data from these two sources appears to converge. The incidence of OME depends very much on the age of the child [12,13]. Our study shows that in children of school age, irrespective of treatment used, the chance of OME persisting beyond 16 months decreases with age--by 47% for every 2 years.…”
Section: Discussionmentioning
confidence: 68%
“…In general, prevalence decreases with age [Suarez Nieto et al, 1983], but a meta-analysis reported peaks at the ages of 2 and 5 years [Zielhuis et al, 1990a]. The later peak is perhaps contributed to by exposure to respiratory infections when children start school, but could also include a shift towards OME rather than AOM, congruent with a theoretically decreasing bacterial ingress.…”
Section: The Effect Of Agementioning
confidence: 91%
“…Those with CSOM often give a history of prior AOM, but AOM is not more frequent in this group compared with the background population [Fliss et al, 1991;Lasisi et al, 2007]. Clinical experience suggests that whereas CSOM may occur subsequent to AOM, in the developed world often it occurs secondary to a history of COME [Suarez Nieto et al, 1983;Youngs, 1998]. In such cases it may be that non-resolving inflammation in COME leads to degeneration [Sadé, 1993;Sano et al, 1994] and eventual perforation of the tympanic membrane, which then allows periodic or persistent infection of dysfunctional mucosa by flora of the external auditory canal [Brook, 1981].…”
Section: Chronic Suppurative Ommentioning
confidence: 99%
See 1 more Smart Citation
“…In Sweden, incidences of 32% in 3‐year olds and 26% in 7‐year‐olds have been reported 12,13 . Suarez Nieto et al 14 showed a fall in prevalence of OME from 38.8% at age 2 years to 1.1% at 11 years of age. OME has a comparatively lower prevalence in underdeveloped and developing African countries.…”
Section: Discussionmentioning
confidence: 99%